Interleukin-6 Secretion in Response to Onopordum jordanicolum Plant Extracts in Prostate Cancer Cells - Al-Bakheit, Ala'a; Abu-Romman, Saeid; Sharab, Ahmad; Al Shhab, Mohammad (Jordan Journal of Pharmaceutical Sciences, 2019)
Onopordum jordanicolum is a Jordanian native medicinal plant with poorly investigated anti-inflammatory properties. The current study aimed to explore the anti-inflammatory effect of Onopordum jordanicolum in in vitro cell models of human lung fibroblast non-cancer MRC-5 and prostate cancer PC3 cells through measuring lipopolysaccharide-induced interleukine-6 secretion. The cells were treated with the plant water and methanol extracts for 72hrs prior to lipopolysaccharide exposure for 24hrs. The cytotoxicity of the plant extracts was measured using the viability assay water-soluble tetrazolium (WST-1). We observed that the plant water and methanol extracts did not decrease lipopolysaccharide-induced interleukine-6 secretion in fibroblast non-cancer MRC-5 and prostate cancer PC3 cells. However, 15.6µM plant water extract showed an anti-inflammatory trend in both cell lines. The plant water and methanol extracts were not associated with toxic effect in the investigated cells. In conclusion, Onopordum jordanicolum did not have anti-inflammatory effects in non-cancerous fibroblasts and prostate cancer PC3 cells.